Modelado Matemático: Estrategia didáctica en la resolución de problemas - Cabrera Calle, Paola Johanna (2024)
The general objective of the Curricular Integration Work entitled "Mathematical Modeling: didactic strategy in problem solving" is: "To contribute to problem solving using mathematical modeling as a didactic strategy in students of fifth year of EGB at the Educational Unit "Lauro Damerval Ayora"; it is a descriptive type of research, with a mixed approach and quasi- experimental design; the theoretical framework addresses the variables: mathematical modeling and problem solving; in the research process the following methods were used: scientific, descriptive, analytical, synthetic and statistical: scientific, descriptive, analytical, synthetic and statistical; the collection of information was done through a diagnostic evaluation designed based on the contents of the prioritized curriculum of 2022 of the intermediate sub- level of basic education and an interview applied to the teacher; the investigated population comprises twenty-four students and a teacher of Educational Unit "Lauro Damerval Ayora"; The initial results show the need to undertake improvement actions in mathematical problem solving, for which the didactic proposal called "Journey to the Wonderful Planet of Mathematics" was planned and successfully implemented. Its effectiveness was corroborated with the second application, whose data show significant changes, so it is concluded that Mathematical Modeling is an interesting and effective pedagogical tool for the improvement of the teaching-learning process of Mathematics, focusing on the development of problem solving and critical thinking skills.